Random matrices and matrix models: The JNU lectures - Mehta, Madan Lal (Pramāṇa, 1997)
A course of lectures was given at the Jawaharlal Nehru University and the Jamia Milia Islamia, New Delhi, during February—March 1996. The following notes were distributed to the audience before each lecture. These notes, which are sketchy and do not go in details, were meant to help students follow the standard literature on the subject. They are collected here (with the exercises!) in the hope that they might prove useful to a larger community of research workers.